How Artificial Intelligence Generated Content can be Effectively Regulated: A Technological Governance Framework Based on Algorithm, Data, and Computing Power - Hualin Zhang; Kun Bi; Li Tian (International Telecommunications Society (ITS), 2024)
Artificial Intelligence Generated Content (AIGC) encompasses content classification, production methods, and technologies for automated content generation. The emergence of ChatGPT has accelerated the growth of AIGC, emphasizing the need for proper governance to prevent crises. The technical advancement of AIGC has revolutionized media content and production mechanisms, challenging traditional governance paradigms. This study delves into the technical aspects of AIGC governance, focusing on algorithms, data, and computational power. AIGC relies on massive data collection, iterative digital modeling, and large-scale computation for autonomous content generation, reflecting its evolution to maturity. A tailored governance framework will guide future AIGC development effectively.
Keywords: 330; Artificial Intelligence Generated Content; Technological Governance; Governance Framework; Digital Transformation